2015
DOI: 10.1111/lam.12419
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and kinetic characterization of recombinant 1,3-β-glucanase production in Escherichia coli K-12 strain BL21/pETSD10 - a bioreactor scale study

Abstract: The results contribute to the knowledge of cultivation parameters of E. coli K-12 strain BL21/pETSD10 on a bioreactor scale to overproduce an enzyme degrading β-1,3-glucans. The optimal values of protein concentration, specific activity and total glucanase activity as a function of aeration and stirring were evaluated by numerical analysis. The obtained values were validated as positive. The protein degrades some bonds in hemicellulose. Thus, the protein could be applied as one of the degrading components for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The most important result obtained here was that the highest β-NGF production was achieved at moderate %DO (20%) and post induction temperature of 32°C. These results are in agreement with the previous data presented by others on the production of various proteins in E. coli in the bioreactor scale (Zaslona et al 2015).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The most important result obtained here was that the highest β-NGF production was achieved at moderate %DO (20%) and post induction temperature of 32°C. These results are in agreement with the previous data presented by others on the production of various proteins in E. coli in the bioreactor scale (Zaslona et al 2015).…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, at high degree of DO as a result of high agitation speed break down of the cells takes place (Banerjee et al 2009). Recently, Zaslona et al (2015) showed that production of recombinant 1,3-β-glucanase in E. coli increased when moderate stirring and oxygenation was applied. Therefore, to evaluate the effects of %DO and post induction temperature on β-NGF expression level and cell growth rate, we used response surface methodology (RSM) as a high effective method (Elibol and Ozer 2002;Wejse et al 2003;Rui et al 2009).…”
Section: Discussionmentioning
confidence: 99%